Kajian Pengendalian Hazard terhadap Keselamatan Operasional di Apron Bandara Internasional Juanda Surabaya - Muchamad Nur Syaifulrahman; Dwi Afriyanto; Alwazir Abdusshomad (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
This study aims to identify various types of hazards found in the Apron of Juanda International Airport Surabaya and analyze their impact on flight operational safety. The apron is a vital area in aviation activities because it is a parking lot for aircraft, the process of boarding and dropping passengers, loading and unloading cargo, and light maintenance activities. The existence of potential hazards in this area can have a direct effect on flight safety if not handled properly. The research method used was qualitative descriptive with data collection techniques through field observations, interviews with apron officers, and documentation during the implementation of On The Job Training. The data obtained is then analyzed to identify potential hazards and evaluate the level of risk. The results of the study show that there are still hazard findings in the apron area, including Foreign Object Damage (FOD) in the form of foreign objects that have the potential to damage aircraft engines, oil or fuel spills that can cause fires, the presence of wild animals in the aircraft movement area, Ground Support Equipment (GSE) that is parked out of place so as to interfere with aircraft movement, and marshalls who do not use Complete Personal Protective Equipment (PPE).  This problem is caused by the weak supervision of the Apron Movement Control (AMC) unit and the low awareness of personnel in implementing a work safety culture. Based on these findings, the author prepared mitigation measures in accordance with the guidelines of Doc 9859 AN/474 concerning the Safety Management Manual, including increasing supervision, enforcing safety standards, and periodic training for all apron personnel. It is hoped that the results of this study can be an evaluation reference for airport management to strengthen the supervision system, reduce the risk of accidents in the apron area, and build a better and sustainable work safety culture.